2022
DOI: 10.1097/mcc.0000000000000961
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition before, during and after critical illness

Abstract: Purpose of reviewThis review describes considerations preintensive care unit (ICU), within ICU and in the post-ICU period regarding nutrition management and the current state of the literature base informing clinical care.Recent findingsWithin ICU, studies have focussed on the first 5–7 days of illness in mechanically ventilated patients who are heterogeneous and with minimal consideration to premorbid nutrition state. Many evidence gaps in the period within ICU remain, with the major ones being the amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…However, energy and protein intake should likely be further increased during convalescence when inflammation resolves and elevated muscle protein breakdown rates decrease, particularly when combined with physical activity [43]. Several studies have shown poor feeding performance among post-ICU patients (50–70% of energy and protein adequacy) [1,44 ▪ ], highlighting the need for specific interventions. Inadequate intake in the post-ICU phase is multifactorial [44 ▪ ,45].…”
Section: Post-icu Nutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, energy and protein intake should likely be further increased during convalescence when inflammation resolves and elevated muscle protein breakdown rates decrease, particularly when combined with physical activity [43]. Several studies have shown poor feeding performance among post-ICU patients (50–70% of energy and protein adequacy) [1,44 ▪ ], highlighting the need for specific interventions. Inadequate intake in the post-ICU phase is multifactorial [44 ▪ ,45].…”
Section: Post-icu Nutritionmentioning
confidence: 99%
“…Critical care nutrition is a rapidly evolving field in which significant steps have been made toward nutritional recommendations specific to each patient. This shift allows healthcare providers to consider the patient's characteristics, medical diagnosis, current treatments, and metabolic state [1]. The multifactorial nature of nutritional needs in critically ill patients and the difference in outcomes and methodologies assessed in available studies pose challenges to establishing fitting guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…As feeding is already initiated for most patients in the ICU, it is important to reassess their special nutritional needs following transfer to the medical ward. This process requires the multidisciplinary cooperation of all involved personal to ensure optimal continued care [2].…”
Section: Feeding Strategy and Nutritional Support In The Recovery Pha...mentioning
confidence: 99%
“…Implementation of guidelines in clinical practice remains challenging. Nutritional feeding protocols must be continued and adapted once patients survive the acute phase of illness and transition to the medical ward for recovering phase [2]. Subsequently, patients may transition to a rehabilitation phase, which can also last for months [3].…”
Section: Introductionmentioning
confidence: 99%
“…It is critical to look into how diet affects clinical and functional outcomes across hospitalization and to use interventions in ways that are biologically likely to have an impact. Individualized nutrition plans, longer-lasting therapies, oral nutrition assistance, and the use of newly developed bedside body composition tools to detect patients at nutritional risk are all areas that hold promise for the future of critical care nutrition (18).…”
Section: Prevention and Management Of Malnutritionmentioning
confidence: 99%